2019
DOI: 10.1093/inthealth/ihz116
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of violence against women in Panama: results from population-based cross-sectional studies and a femicide registry

Abstract: Background We aimed to investigate the prevalence of violence against women (VAW) in Panama and its association with social determinants of health (SDH) and to estimate the femicide rates from 2014 to 2017. Methods Data were derived from three cross-sectional population-based studies. Logistic regression models were used to estimate the association between SDH and VAW, expressed as odds ratios (ORs) and 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…This result is different from previous data from Ecuador where both a higher prevalence of physical and sexual IPV was reported among Indigenous women [ 6 ]. In the study from Panama, physical or sexual IPV were more common among Indigenous [ 36 ], which contradicts our results. A Mexican study reported that societies with an Indigenous minority had higher prevalence of IPV in comparison to societies that were exclusively Indigenous, indicating that being part of a minority group can be a risk factor for VAW [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This result is different from previous data from Ecuador where both a higher prevalence of physical and sexual IPV was reported among Indigenous women [ 6 ]. In the study from Panama, physical or sexual IPV were more common among Indigenous [ 36 ], which contradicts our results. A Mexican study reported that societies with an Indigenous minority had higher prevalence of IPV in comparison to societies that were exclusively Indigenous, indicating that being part of a minority group can be a risk factor for VAW [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Non-partner sexual violence in younger ages seems to be a common finding [ 6 , 12 , 13 , 35 ] with the perpetrator typically a family member or a male known to the victim [ 35 ]. Although age was not associated with IPV in the Bolivian study [ 14 ], it played a role in a recent study from Panama [ 36 ] where younger women reported more frequently physical or verbal violence by any perpetrator during the past year. The role of age as an associated factor seems to be very contextual and related to the type of violence, with studies showing no association [ 14 ], higher risk among youth [ 26 , 36 ] or among older age groups [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social constructs that determine the risk of VAW include poverty, low educational obtainment, gender‐based social roles, lack of self‐determination of one's future, prioritization of food sharing in the family, as well as the literal value of a female in the form of a marital dowry (Skolnik, 2016 ). Loss of social supports and inadequate punitive measures for violent crimes are predictors of VAW (Merson et al., 2012 ; Santamaria et al., 2019 ), as well as alcohol and firearms use among males (Merson et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%